2003
DOI: 10.2337/diabetes.52.3.614
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Fatty Acids Released From Lipolysis of Plasma Triglycerides to Total Plasma Fatty Acid Flux and Tissue-Specific Fatty Acid Uptake

Abstract: There is controversy over the extent to which fatty acids (FAs) derived from plasma free FAs (FFAs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
2
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 33 publications
6
111
2
3
Order By: Relevance
“…Nonetheless, the infusion of either triglyceride or free fatty acid bound to albumin does not appear to affect the kinetics of tracer movement from the plasma compartment into heart (4, 47, 52). The rapid interchange of fatty acids hydrolyzed from triglycerides with the free fatty acid pool negates any difference between these two different routes of delivery (47). Furthermore, infusion of [1-3 H]hexadecanol has been used to quantify the kinetics of heart ether-lipid biosynthesis (15) and indicate that the use of high-specific-activity radiotracers was successful in estimating heart lipid biosynthesis or fatty acid uptake (4,35,36,47,52).…”
Section: Animalsmentioning
confidence: 99%
“…Nonetheless, the infusion of either triglyceride or free fatty acid bound to albumin does not appear to affect the kinetics of tracer movement from the plasma compartment into heart (4, 47, 52). The rapid interchange of fatty acids hydrolyzed from triglycerides with the free fatty acid pool negates any difference between these two different routes of delivery (47). Furthermore, infusion of [1-3 H]hexadecanol has been used to quantify the kinetics of heart ether-lipid biosynthesis (15) and indicate that the use of high-specific-activity radiotracers was successful in estimating heart lipid biosynthesis or fatty acid uptake (4,35,36,47,52).…”
Section: Animalsmentioning
confidence: 99%
“…Infusion of [ 14 C]palmitate-labelled CM into rats demonstrated substantial CM-TAG oxidation which was decreased only slightly (16%) by co-administration of glucose, implying a preference for CM-TAG oxidation [6]. High rates of label retention of CM prepared from chyle lymph were found in heart (more than skeletal muscle though less than white adipose tissue), and about 3 fold higher than NEFA; the ratio of TAG retention to NEFA retention was higher in heart than other tissues, suggesting a strong cardiac preference for TAG [7]. Gousios [8] perfused rabbit hearts with d<1.006 lipoproteins containing labelled TAG (a density corresponding to both CM and VLDL) and found fractional extraction rates of 15% in the fed state and 30% in hearts from fasted animals.…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…Infusion of labelled CM-TAG into mice found that 80-90% of the TAG-FA was recovered from plasma, and TAG lipolysis contributed 10-20% of total plasma FA turnover [7]; given the substantial cardiac TAG-FA assimilation in these experiments, the authors proposed a model of very high local FA released from CM-TAG lipolysis [7]. T CM-TAG is seen in physiologic and pathologic situations of metabolic perturbation and redistribution of plasma substrates.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations